Of Military Chaplains and Mass at Sea: Politics and Religion in The Spanish Navy During the Second Republic - González González, Alberto (Hispania Nova, 2024)
The 1930s witnessed a change in the understanding of religion and the place it should fill in Spanish society. The Second Republic, proclaimed in 1931, had the intention of moving everything related to religious beliefs to the private sphere. Accordingly, the presence of the Church in the various state institutions was limited, before subsequently disappearing altogether. This also applied to the Spanish Navy where, among other acts, the number of chaplains was reduced prior to the elimination of the ecclesiastic corps, boat launches ceased to be blessed, services in centres and on ships and official attendance at religious events were prohibited, and the holiday for the Virgin of the Carmen, was abolished. This article reviews the measures issued by the central government in this respect and the way in which they were adhered to.
Keywords: Spanish Navy; Second Republic; military chaplains; secularization; religiosity